The Existence and Implications Of Land Bank Regarding The Ruling Of The Constitutional Court No. 91/PUU-XVIII/2020 On The Formal Test Of The Job Copyright Law - Anwar, Khoirul; Irawan, Dhyan Andika; Rifai, Ahmad (Rechtsvinding, 2025)
The existence of a Land Bank is regulated by Article 125 to Article 135 of the Job Creation Law. Subsequently, a formal test was carried out on the Job Creation Law by the Constitutional Court, which in the Constitutional Court Decision No. 91/PUU-XVIII/2020, stated Law no. 11 of 2020 concerning Job Creation was declared formally flawed. In the seventh point of the Constitutional Court Decision No.91/PUU-XVIII/2020 dated 25 November 2021 it explicitly states the suspension of all government actions/policies that are strategic in nature and have broad implications, including the new implementing regulations of the Job Creation Law. The government is ordered to make improvements, within a maximum period of two years and if within that time no improvements are made, the Job Creation Law will become permanently unconstitutional. Even though the Constitutional Court's decision states that the Job Creation Law is still valid, it has no binding force. The method used in this study is a normative juridical approach, namely testing and tracing related to laws and regulations. The purpose of this study is to find out the existence and implications of the Land Bank institution, especially its derivative regulations related to the Constitutional Court Decision No.91/PUU-XVIII/2020 which states conditional unconstitutionality of the Job Creation Law, including the implementation of the Land Bank which is included in the category of strategic policies and has wide-reaching impacts according to the sound Article 4 of Law No. 11 of 2020 and the Constitutional Court's decision.